Implementation Of Islamic Change Management On Employee Performance - Syafira, Dinda (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
Changes, both planned and unplanned, will always occur in human life at every stage. Because change is the nature of man as a creature, he changes from the time he is in his mother's womb until he is born and grows into adulthood and even old age. Change will not be distinguished from institutions or organisations in the same way. The role of a leader will have a significant impact on organisational development and change. An ideal leader will be able to bring appropriate, conditional, and purposeful changes to the organisation that he or she oversees. The led institution will be able to achieve its goals maximally if the changes are implemented and managed in a structured and methodical manner.